Optimal allocation of cloud multi-tenant platform infrastructure resources. (10th May 2019) - Ignatyev, Oleksiy
Infrastructure resources optimisation is a significant challenge in multi-tenant cloud environment. A system and associated algorithm and processes to enable a multi-tenant platform operator or administrator to make more optimal decisions with regards to the allocation of platform infrastructure resources (such as computational capabilities, data storage, etc.) among one or more tenants or accounts are provided. In particular, we construct a data 'signature' for a set of identified users, accounts, or tenants, where the signature contains data regarding the user, account, or tenant's 'consumption' of platform infrastructure resources. Later tenants 'signatures' are being used to accomplish cloud infrastructure resources optimisation in multi-tenant environment. An innovative algorithm for cloud infrastructure resources optimisation in multi-tenant environment is introduced in current paper.